Processos de mediação de conceitos algébricos durante o uso de um objeto de aprendizagem - Leite, Monalisa de Abreu (2006)
The present research aims to analyze the dialogical exchanges between teacher and students while using a Learning Object designed to help students understand algebraical concepts. The study was conducted with a 7th grade class and his math teacher in a public school at Fortaleza, Brazil. An analysis was conducted on the use of a learning object called Interactive Scale which intends to work on concepts of equation, inequality and unknown. The study was grounded on authors such as Vygotsky (1998, 2003) who discusses the ideas of mediation e interaction; Valente (1998), Carraher (1992), Gomes (2000), Castro-Filho et al. (2003, 2005) e Peres (2002) who deal with use of educational software and the development of mathematical concepts mediated by interactive tools. The research methodology was qualitative, based on the conversational analysis (Marchusci, 1991), Microgenetic analysis and videography (Meira, 1994) in the data collection and analysis. Results shown that the dialogical exchanges between teacher and students during the Learning Object use were related to the understanding of mathematical concepts, particularly the notions of equation, inequality and unknown. There was also a continuity of actions among the participants which suggests that teacher mediation guided the activities.